PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA UNTUK MENSUKSESKAN PENYALURAN DANA DESA DI DESA SUNGAI GUNTUNG TENGAH KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Iskandar, Yenny; Windartini, Sry; Suharmiyati, Suharmiyati (LPPM Press STIE Indragiri Rengat, 2019)
This research was conducted at office Desa Sei Guntung Tengah,  Kecamatan Rengat  Kabupaten Indragiri Hulu. The aim is to determine the effect of Compensation on the performance of village officials in the success of Village Fund Distribution in desa Sungai Guntung Tengah, Kec. Rengat, Kabupaten Indragiri Hulu. The results of the study obtained by linear regression equation is that SPSS knows that constant (a) is 1.361. and the coefficient of X (b) is 0.355 with a multiple regression equation is Y = 1.361 + 0.355 X. The correlation coefficient is known that (X) compensation has a relationship with (Y) the performance of village officials. This can be seen from the value of the multiple correlation coefficient R is 0.813 meaning that it has a very strong and direct relationship. and then tested with a multiple coefficient of determination (R2) is 0.661. this shows (X) compensation can contribute to the variable (Y) the performance of the village apparatus by 66.1%. And the remaining 33.9% is influenced by other variables not examined in this study. t count for compensation variable is 2.239, in table t with db 35 and significant level 0.025 is obtained 2.034. because t count (2,239)> from t table (2,034) then Ho is rejected and Ha is accepted, which means compensation has a significant influence on the performance of the village apparatus.